Ethnography and inequality - Baumann, Benjamin; Strauß, Sophie; Zehmisch, Philipp (Global handbook of inequality, 2024)
What is ethnography and how does it relate to questions of inequality? Outside the discipline of sociocultural anthropology, ethnography is increasingly conflated with anthropological fieldwork, the discipline’s signature method and ideological paradigm. Thereby, ethnography tends to be imagined as less unequal than other methodological paradigms in the humanities and social sciences. Current disciplinary conventions and traditions of self-representation compel anthropologists to perpetuate the myth of ethnography as an encounter between researchers and study subjects at eye level. However, this is just one of several professional myths surrounding ethnography as methodological paradigm and textual genre. While this chapter seeks to unravel some of these myths, the authors will also introduce approaches such as subaltern theory that contain promising potentials to address the inequalities that characterize the ethnographic project. At the same time, the authors admit that these approaches ultimately fail to undo the epistemic inequality implied in any ethnographic endeavour. Hence, they maintain that sociocultural anthropology’s defining and almost canonic methodological assemblage, which is routinely subsumed under the umbrella term ‘ethnography’, builds on a heuristic that presupposes different forms of inequality. Despite visionary calls for decolonizing the discipline, it is argued that sociocultural, political, economic and epistemic inequalities remain core components of fieldwork and writing up that are continuously perpetuated by anthropologists as long as ‘ethnography’ remains the key to their disciplinary practice.
Gesehen am 04.07.2024